Let ( x 1 , y 1 ) , ( x 2 , y 2 ) , … , ( x n , y n ) be the real solutions to the system of equations
x + x 2 + y 2 3 x − y = 3 y − x 2 + y 2 x + 3 y = 0
Evaluate: i = 1 ∑ n x i + y i
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The fractions are in the way, how do we get rid of them?
We will attempt to multiply the first equation by y and the second equation by x . Adding the new equations, we have 2 x y + x 2 + y 2 − ( y 2 + x 2 ) = 3 y
Or 2 x y − 1 = 3 y . Solving for x , we have x = 2 y 3 y + 1
Substituting x = 2 y 3 y + 1 to our second equation and simplifying, we have 4 y 4 − 3 y 2 − 1 = 0 ⟹ ( y 2 − 1 ) ( 4 y 2 + 1 ) = 0 ⟹ y = ± 1
If y = 1 , we have x = 2 . If y = − 1 , we have x = 1 . So the solutions are ( 2 , 1 ) and ( 1 , − 1 ) for x and y , respectively.
Therefore i = 1 ∑ n x i + y i = 2 + 1 + 1 − 1 = 3
Note: There is a nice approach if you consider the complex number z = x + i y , and find the corresponding cubic equation.
I think it should be Level 4 question
What about complex roots? x = 2 3 ± i works as well.
Log in to reply
Clarified. I was thinking that it was understood to be real solutions since we weren't given any conditions (like on contests). So next time, I'll be specific.
Problem Loading...
Note Loading...
Set Loading...
The equations given are the real and imaginary parts of x − y i + x − y i 3 + i = 3 . Let z = x − y i ; then z 2 − 3 z + ( 3 + i ) = 0 , which factors as ( z − ( 2 − i ) ) ( z − ( 1 + i ) ) = 0 . So z = 2 − i or z = 1 + i , which leads to ( 2 , 1 ) and ( 1 , − 1 ) as the two solutions. The sum of the coordinates is 3 .